Examining the Relationships between Self-Efficacy, Effort Regulation Strategy Use, and English Vocabulary Skills - Sakae Onoda (Studies in Self-Access Learning Journal, 2014)
This study explores the relationships among self-efficacy beliefs, effort regulation strategies, and English vocabulary development at a university in Japan. The theoretical framework draws on Pintrich and Zusho’s (2002) model of self-regulation, motivation, and academic success and Bandura’s (1986) social cognitive theory.